REGULARITIES OF DISTRIBUTION BY MELTING AND BOILING POINT OF SIMPLE SUBSTANCES AND CHEMICAL COMPOUNDS AND THEIR RELATIONSHIP WITH OTHER PHYSICAL AND CHEMICAL PARAMETERS: DOI: https://doi.org/10.17721/1728-2209.2018.1(55).2 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
Investigated in large sample (over 2770 objects) the patterns of relationship between melting points (TM) and boiling point (TB) of simple substances (chemical elements) and different chemical compounds, inorganic and organic nature. The detected temperature ratio parameter to correlation with amount of molar volume (VE) and specific density (dE) for the 118 today known elements. Found the strict formula mating with other physical-chemical parameters and constants. Able to predict and refine TM, TB, VE and dE of the chemical elements all Tran's uranium series.It is show that the correlation equations of lines of distribution of simple substances (chemical) compounds of organic and inorganic nature in the form of functions: ТM = f (∆ТMB), ТB = f (∆ТMB), where ∆ТMB = (ТB-ТM), and the boundaries of their special zones clearly correlated to the level of simple mathematical formulas with the fundamental constants. In particular next constant: the fine structure (αo = 0.0072973524;  constant of gravitation (G = 6,67428×10–11 m3·(c·kg)–2; the electric impedance (Zo = cµo = 376,73031); a molar volume (Vo = 0.0224139682 m3·k-mol–1; a specific energy chemical connection ∆Go = 395458,1716 J·mol–1; and gravity radius (equally weighted according to Kepler's laws) r8 = 1467,584624 m, and others.It is also shown that areas of selected points (Тi) on the function of the ТM = f (∆ТMB), for which ТM = Тi, the approximation lines on the function of ТB = f (∆ТMB), are linear in nature. This lines have characteristic coefficients: y = 1,00092660467x + 302,179177315 , and tangent of an angle whose angle to the axis of the horizontal axis tg(a)К = 1,0016259582, the simple ratio of universal physical-chemical molar volume constant [(tg3a)К / (2·103)]½   ≈ Vo = 0,0224139682 m3·k-mol–1.Found almost simultaneous move two periodicals dependencies molar volume VE elements and their temperature coefficient kt = (ТB + ТM) / (ТB – ТM) from the sequence number of the chemical elements. Based on this fact, was made the forecast values of VE, and calculated on the specific density (dE) t of the all elements Tran's uranium series items. Experimental determinationConducted a comparison of the stability of atoms and stars on the example of the analysis of the periodic dependence of the specific density (dE) all of the 118 known elements today from their serial number. Also was the proposed graduation of four a limited bounders, and eight zones of stability to the same a stars stability of the transitions in similar vision in accordance with the periodic changes in the properties of the respective chemical elements with same mass multiplicity sight for cosmological masses.  Namely, for the stars - MÜ = MЕ×M8  same as for the atomic masses same - mЕ = MЕ×mu. In addition, show that limit for atoms and you allow vision grown to the multiplicity of the masses (308 ÷ 312) of the respective units, i.e. sight (MÜ) max = (308 ÷ 312)×M8, as for atoms - (mE)max = (308 ÷ 312)×mu corresponding isotope of the elements with sequential numbers from NЕ with 118 to 126.
Keywords: melting and boiling point, chemical elements, chemical compounds, molar volume, density, fundamental constants, constant of gravitation, fine structure constant, trans uranium elements, the аtom mass limit.